8.2.2 On the Efficacy of Student Teams in Engineering: An Assessment of Individual Learning in Collaborative Projects. Issue 1 (July 2014) - DeFranco, Joanna F.; Neill, Colin J.
Abstract The scale, complexity, and multi‐disciplinarity of systems engineering projects almost necessitate that systems engineers work in teams and that those teams are effective. Consequently, systems engineering students can expect to participate in a number of team projects during their academic careers. It is also reasonable that students can expect their effort on teams to contribute meaningfully to their individual course learning. We have developed a guidance framework that facilitates effective collaboration on teams and previously demonstrated its efficacy in team mental model convergence and its concomitant improvement in team project outcomes. In this study we investigate whether those improved team outcomes lead to an improvement in individual learning as should occur if there is team learning. We determined that this is not the case. The implications of this result are potentially troubling not only from an academic standpoint, since it challenges the validity of student teams in some cases, but also with respect to the professional development programs in place at many engineering companies. These programs are often team‐oriented with the intent of not only developing effective team players, but also in developing proficient engineers and the latter objective may be threatened.